Jean-Luc ARNAUD on Sun, 04 Dec 2022 02:04:01 +0100

[Date Prev] [Date Next] [Thread Prev] [Thread Next] [Date Index] [Thread Index]

I don't find the solution ...


Working with eval, I get the expected result with:

    eval([ a=((6*k)!*(-1)^k)/(((3*k)!*(k!)^3)*640320^(3*k)), k*a ]);

But I don't achieve the same calculation with pareval.

I'm using ()-> for the first equation, but what should I use for the second?

I tried:

    pareval([ (a)->((6*k)!*(-1)^k)/(((3*k)!*(k!)^3)*640320^(3*k)), ()->k*a ]));


    eval([ ()->a=((6*k)!*(-1)^k)/(((3*k)!*(k!)^3)*640320^(3*k)), ()->k*a ]));

The first pareval results in correct calculation of the first term, but the second term is always 0.

Thanks for your help.


Jean-Luc Arnaud